The correlation between the antioxidant and anti-aging activities of Hydrangea serrata Seringe extract - Kim, Seo-Hee; Sun, Sang-Ouk; Yim, Soon-Ho (Food Science and Technology, 2023)
In this study, the correlation between antioxidant and anti-aging activities of Hydrangea serrata Seringe extract was confirmed. Total polyphenol and total flavonoid content were determined to be highest in 60% ethanol extract (11.45±0.13 mg GAE/g) and 40% ethanol extract (19.27±0.09 mg CE/g), respectively. In the reducing power experiment for transition metal ions, the 40% ethanol extract (285.96±0.99 mM TE/g, 5.21±0.99 mM TE/g) was the best for both. In the DPPH and ABTS radical scavenging activity, 80% ethanol extract (5.35±0.00 mM TE/g) and 40% ethanol extract (969.14±0.00 uM TE/g) were the best, respectively. In the ORAC assay, 60% ethanol extract showed the highest antioxidant activity (2.62±1.22 mM TE/g). The RC50 values of the HR and HP experiments showed excellent activity in 20% ethanol extract (631.96±0.6 μg/mL) and 40% ethanol extract (115.62±0.9 μg/mL), respectively, and for active nitrogen evaluation of species elimination efficacy, the 40% ethanol extract (41.03±3.7 μg/mL, 373.10±5.1 μg/mL) displayed strong (ONOO-) scavenging activity. In addition, 40% ethanol extract showed the highest anti-aging activity in the range of 16.40–42.54%. The correlation between reactive oxygen species (HR, HP) scavenging activity, active nitrogen species (NO, ONOO-) scavenging activity, and anti-aging effect (collagenase inhibition) showed significantly high values. It was confirmed that the active nitrogen species scavenging rate has a high correlation with the anti-aging effect.